A study on production, transportation and export activities in Kumpulan Guthrie Berhad's Dynat Rubber / Siti Sadilah Abdul Aziz - Abdul Aziz, Siti Sadilah (1989)
The public always relate the company with its main commodity that is rubber and oil palm. This is because when we travel along the highway from north to south of west of Peninsular Malaysia, we can see the rows of rubber tree and oil palm with marks of "Guthrie" at the estate. The estates are well keep and clean compared to other estates.